3-D analysis of electron beam shape at target plane through parametric variation of an indirectly heated cathode-based electron gun. Issue 1 (1st February 2023) - Goel, V; Roy, A; Maiti, N
Abstract: In this paper, a detailed 3-D analysis of the electron beam shape at the target plane of high power (60 kW, 60 kV, 1 A) 270 0 -bent indirectly heated cathode-based electron gun has been successfully carried out. This work will help analyse individual electron beam trajectories in the actual 3-D plane to ensure optimum electron beam bending and focusing at the target plane. Moreover, due to the presence of an additional electrode in an indirectly heated cathode-based electron gun i.e., a filament which is resistively heated and an indirectly heated solid cathode (heated through electron bombardment), this analysis becomes even more imperative. The work carried out in this paper will ensure better performance, characterization, and optimization of the 270 0 -bent indirectly heated cathode-based electron gun. Rigorous simulation work has been carried out by performing 3-D electrostatic, electromagnetic, and particle tracking simulations using CST Studio Particle Tracking Module. Adaptive mesh refinement has been utilized to ensure high accuracy of the results obtained. An optimum filament-solid cathode interspacing was found, using strip-shaped filament by providing a higher negative potential to the grid cup. It led to a well-focused 270 0 -bent electron beam, exhibiting minimum electron beam emittance at the target plane.